2013
DOI: 10.4236/wjns.2013.32012
|View full text |Cite
|
Sign up to set email alerts
|

Helplessness-like escape deficits of NIH-HS rats predict passive behavior in the forced swimming test: Relevance for the concurrent validity of rat models of depression

Abstract: The genetically heterogeneous NIH-HS rat stock has been characterized by its response to anxiety-and fear-inducing situations, thus leading to the conclusion that they are a rather anxious and passive coping type of rats. Taking advantage of these profiles, and knowing that they show very poor performance in the two-way active (shuttle box) escape/avoidance task, we have tested NIH-HS rats (n = 80) in the forced swimming test (FST) as well as we have studied escape response deficits (i.e. response failures) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…That study demonstrated that the procedure used to generate the genetically heterogeneous stock had been successful, since for most traits related to consumption/effects of ethanol, NIH-HS rats fell approximately in the middle of the high and low values of the eight inbred progenitor strains [5,6]. The neurobehavioral characterization of NIH-HS rats carried out so far in our laboratory includes traits related to unconditioned and conditioned anxiety/fear, exploratory behavior and coping style, as well as hormonal sensitivity to stress and central gene expression [7][8][9][10][11][12][13][14][15][16][17][18]. These studies have led to the conclusion that the genetically heterogeneous rat stock displays relatively elevated anxiety/fear (as shown by unlearned and learned anxiety tests/tasks) and enhanced hormonal responses to stress, as well as a predominantly reactive (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…That study demonstrated that the procedure used to generate the genetically heterogeneous stock had been successful, since for most traits related to consumption/effects of ethanol, NIH-HS rats fell approximately in the middle of the high and low values of the eight inbred progenitor strains [5,6]. The neurobehavioral characterization of NIH-HS rats carried out so far in our laboratory includes traits related to unconditioned and conditioned anxiety/fear, exploratory behavior and coping style, as well as hormonal sensitivity to stress and central gene expression [7][8][9][10][11][12][13][14][15][16][17][18]. These studies have led to the conclusion that the genetically heterogeneous rat stock displays relatively elevated anxiety/fear (as shown by unlearned and learned anxiety tests/tasks) and enhanced hormonal responses to stress, as well as a predominantly reactive (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…The genetically heterogeneous NIH-HS rat stock (i.e., “National Institutes of Health Genetically Heterogeneous Rat Stock”) was developed by Hansen and Spuhler ( 1984 ) through an eight-way cross from eight inbred rat strains and they were bred for more than 50 generations. The NIH-HS rats are a unique tool to study the genetic basis of complex traits due to their broad phenotypic variation and high degree of genetic recombination compared to the usual laboratory rat strains (e.g., Spuhler and Deitrich, 1984 ; López-Aumatell et al, 2008 , 2009a , b , 2011 ; Johannesson et al, 2009 ; Vicens-Costa et al, 2011 ; Díaz-Morán et al, 2012 , 2013a , b , c , 2014 ; Baud et al, 2013 , 2014a , b ; Estanislau et al, 2013 ; Palència et al, 2013 ; Alam et al, 2014 ; Tsaih et al, 2014 ). Moreover, NIH-HS rats have been shown to closely resemble RLA-I rats in their coping style and stress sensitivity profiles (e.g., López-Aumatell et al, 2009a ; Díaz-Morán et al, 2012 , 2013c ; Estanislau et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a few studies that observed individual animals suggest that this may be an advantageous approach and that it might be possible to predict the response of a specific animal to a challenge based on its response to other challenges. For example, working with NIH-HS rats, researchers examined helplessness-like escape deficits in a shuttle box and behaviour in the forced swimming test (FST) and showed that at least for the extreme animals, the behaviour in one test predicts the behaviour in the other model (Table 1) (66).…”
Section: Individual Differences Within Groupmentioning
confidence: 99%